Nation and identity - Poole, Ross, 1938- (Ideas (Series) (Routledge (Firm)), 1999)
This provides a concise and comprehensive account of the place of national identity in modern life. Poole offers us a new analysis of the concept of identity, arguing that we are now in a position to envisage the end of nationalism.